Optimum angle-cut of collimator for dense objects in high-energy proton radiography - 许海波 郑娜 (Chinese physics C, 2016)
The use of minus identity lenses with an angle-cut collimator can achieve high contrast images in highenergy proton radiography.This article presents the principles of choosing the angle-cut aperture of the collimator for different energies and objects.Numerical simulation using the Monte Carlo code Geant4 has been implemented to investigate the entire radiography for the French test object.The optimum angle-cut apertures of the collimators are also obtained for different energies.